The Influence of the Work Environment and Work Stress on Employee Performance Case Study at STIE IBMT Surabaya - Iswati, Iswati; Aisah, Siti; Ignatius, Jimmy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to determine the effect of work environment and stress on performance for operational employees at STIE IBMT Surabaya. Where the proposed two independent variables and one dependent variable, namely the working environment and job stress acting as independent variables and employee performance served as dependent variables. This research was conducted using a survey of operational employees in the import and export service company was analyzed by regression. The first phase of testing the validity and reliability of questions of each variable. The second phase, making the regression variable work environment and work stress on employee performance. The results showed that the variable has a significant positive work environment on the performance of employees in decline. And work stress variables significant negative effect on employee performance in decline. However, work stress are at low to moderate level will create a good employee performance and will worsen if the employee within a very long time and excessive.